Preventive Effect of Salicylate and Pyridoxamine on Diabetic Nephropathy - Tarek Kamal Abouzed; Seiichi Munesue; Ai Harashima; Yusuke Masuo; Yukio Kato; Khaled Khailo; Hiroshi Yamamoto; Yasuhiko Yamamoto (Journal of Diabetes Research)
Objective. Diabetic nephropathy is a life-threatening complication in patients with long-standing diabetes. Hemodynamic, inflammatory, and metabolic factors are considered as developmental factors for diabetic nephropathy. In this study, we evaluated whether pharmacological interventions with salicylate, compared to pyridoxamine, could prevent diabetic nephropathy in mice. Methods. Male mice overexpressing inducible nitric oxide synthase in pancreatic β-cells were employed as a diabetic model. Salicylate (3 g/kg diet) or pyridoxamine (1 g/L drinking water; ~200 mg/kg/day) was given for 16 weeks to assess the development of diabetic nephropathy. Treatment with long-acting insulin (Levemir 2 units/kg twice a day) was used as a control. Results. Although higher blood glucose levels were not significantly affected by pyridoxamine, early to late stage indices of nephropathy were attenuated, including kidney enlargement, albuminuria, and increased serum creatinine, glomerulosclerosis, and inflammatory and profibrotic gene expressions. Salicylate showed beneficial effects on diabetic nephropathy similar to those of pyridoxamine, which include lowering blood glucose levels and inhibiting macrophage infiltration into the kidneys. Attenuation of macrophage infiltration into the kidneys and upregulation of antiglycating enzyme glyoxalase 1 gene expression were found only in the salicylate treatment group. Conclusions. Treatment with salicylate and pyridoxamine could prevent the development of diabetic nephropathy in mice and, therefore, would be a potentially useful therapeutic strategy against kidney problems in patients with diabetes.